The Challenges of Adopting M-Learning Assistive Technologies for Visually Impaired Learners in Higher Learning Institution in Tanzania - Kamaghe, Juliana Samuel; Luhanga, Edith Talina; Kisangiri, Michael (International Journal of Emerging Technologies in Learning (iJET), 2020)
In the past decades, the world has experienced major changes in the advancement of learning technologies which has enabled learners to engage in their learning activities anywhere. The penetration of mobile phone internet users in Tanzania has been increasing from 2 million in 2011 to 23mil in 2017 The adoption of mobile-based learning (M-learning) for students who are visually impaired in Tanzania has become a major bottleneck since most of the e-learning contents assume that learners have sight and thus include a lot of visualizations. This causes visually impaired students in higher learning Institutions (HLIs) to face challenges such as technical knowledge gaps. Lack of skills and inaccessibility of online contents, which then lead to drop out of the university. The aim of this study is to determine the awareness and usage levels of existing mobile assistive technologies for visual impairment, and the remaining challenges that visually impaired students face, when using such tools on smartphones to access m-learning content from HLIs. in Tanzania. The research was conducted an observational and contextual inquiry study at three major HLIs. We found that 67% of respondents did not have knowledge of m-learning assistive technologies, and their technology barriers for visually impaired students. Also, knowledge, accessibility of Assistive technology and affordability can hinder the adoption of m-learning in Higher Learning Institutions